Wajah peradaban Barat : dari hegemoni Kristen ke dominasi sekular-liberal - Husaini, Adian, 1965-; Wan Mohd. Nor Wan Daud (Jakarta : Gema Insani, 2005)
Influence of Western civilization on Islamic thought in Indonesia
Includes bibliographical references [p. 393-403] and index
Keywords: Islam -- Indonesia -- Western influences; Islam -- Influence; Indonesia -- Civilization -- Western influences